The Study on Time Setting Optimization of Lathe Tool bits for Turning Operations - Hamid bin Salamon; bin Mokhtar, Mohamad Nazri (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
The efficiency of lathe operations in a mechanical workshop heavily depends on the time taken to set up tool bits. This research investigates the time-setting aspect of tool bits during turning operations and proposes improvements to reduce downtime and increase productivity. Data were collected by observing conventional tool bit changes and comparing them with Quick Change Tool Post (QCTP) systems. The findings show that adopting QCTP significantly reduces tool setting time, enhances precision, and improves workflow. Recommendations for implementation and further research are provided to aid workshops in upgrading their processes efficiently.